Determinación de la presencia del virus de Newcastle e influenza aviar en aves silvestres de Humedales de la provincia Zamora Chinchipe - Quezada Chamba, Jhon Fernando (2017)
The objective of the study was to establish the presence of Newcastle virus and avian influenza in wild birds of wetlands of the province Zamora Chinchipe near poultry production. To determine the sampling sites, we used information from the poultry census of 2015 (AGROCALIDAD), which records of the place where there is poultry production. This data was uploaded to academic software ARCGIS which is a Geographic Information System to generate specialized information for the sampling points. El tamaño de la muestra se determinó aplicando la fórmula de prevalencia límite 1% (Gonzalez 1986). Samples of fresh feces were collected from various avian wild species, from which it was processed for viral isolation by inoculation in embryonated 10-day old SPF chicken eggs. Statistical analysis was performed by calculating 95% confidence intervals using the statistical program "R" Studio. The province was divided into three zones, north, central and south. We analyzed 300 samples, the estimated prevalence was 0% with a confidence interval of 0 to 1.19%. In the present study it was not possible to isolate Newcastle disease virus and avian influenza in wild birds in the months of January to February 2016, possibly the birds of the province have not been exposed to the virus of these diseases, however the risk factors are focused on the permanent presence of migratory birds especially in the Podocarpus reserve, another risk factor is the mobility shown by the birds that can transport the virus from one place to another.